Chikungunya no Brasil: modelagem matemática e simulações da dinâmica de transmissão da doença - Felipe, Néder Soares (Universidade Federal de São Carlos, 2024)
Chikungunya is a viral disease primarily transmitted by Aedes aegypti mosquitoes. Since its introduction in Brazil in 2014, the disease has spread rapidly, becoming a significant public health problem. This study aims to explore the transmission dynamics of Chikungunya in Brazil through mathematical modeling. We use compartmental models to describe and predict the disease’s spread, formulating ordinary differential equations solved by the numerical Euler method. The methodology also included estimating the model parameters, fitting them to actual observational data. The results demonstrate that the developed model can replicate aspects of the transmission dynamics of Chikungunya, identifying critical factors that influence its spread. We conclude that mathematical modeling is an essential tool for formulating public policies and more effective control strategies, significantly contributing to the epidemiological understanding of Chikungunya in Brazil.
Chikungunya in Brazil: mathematical modeling and simulations of the disease transmission dynamics
Keywords: Chikungunya; Aedes aegypti; Epidemiologia; Epidemiology; Modelagem Matemática; Mathematical Modeling; Equações Diferenciais; Differential Equations; Métodos Numéricos; Numerical Methods; CIENCIAS EXATAS E DA TERRA::MATEMATICA; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::MATEMATICA DA COMPUTACAO::MODELOS ANALITICOS E DE SIMULACAO; CIENCIAS EXATAS E DA TERRA::MATEMATICA::MATEMATICA APLICADA